PENGARUH MAGNESIUM TERHADAP KEKERASAN DAN KETAHANAN AUS KOMPOSIT ALUMINIUM 6061/nano-Al2O3 DENGAN METODE STIR CASTING - Rochmad Eko Prasetyaning Utomo; Salahuddin Yunus; FX Kristianta (ROTOR, 2016)
Aluminum composite 6061/nano-Al2O3 is a material that utilizes aluminum 6061 as a matrix. Aluminum 6061 is aluminum alloys with magnesium. The mechanical properties of aluminum 6061 are lower than the steel. To increase the mechanical properties of aluminum 6061, nano-Al2O3 particle is added as reinforce. Problems encountered in the manufacture of these composites are the bond between the matrix and the reinforcement. Aluminum 6061 and nano-Al2O3 cannot form a bond each other so it is necessary to add a wetting agent to improve bonding between aluminum 6061 and nano-Al2O3. Wetting agent used in this study is magnesium with purity levels reached 99%. The magnesium is added by 1%, 3% and 5%. Stir casting process is used in this study in order to mix aluminum, alumina and magnesium evenly. Then hardness test and wear test are performed to determine the mechanical properties of the composite 6061/nano-Al2O3. The results show that the hardness is increased about 44 HRB with adding magnesium of 5%. The wearing resistance is also increased which is marked by the lower rate of the wear until reached 2.86 x 10-3 mm3/m. Keywords: Komposit Al 6061/nano-Al2O3, Magnesium, Stir Casting, nano- Al2O3, Al 6061